Meat Quality Assessment for Meatball Production: Influence of Sales Volume Category and Location - Hassani, W. A. I.; Hikmah, H.; Maruddin, F. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
Meat is an essential food ingredient for meeting people's nutritional needs. According to the 2023 meat outlook data, 79.51% of total beef and 35.47% of total chicken meat are utilized by the food industry. Variations in meatball product quality may result from differences in the quality of meat raw materials. This study aims to evaluate the quality of meatball raw materials sold in the markets of Makassar City. This research employed a comparative observational design by collecting 100gram samples of chicken meat and frozen meat/heart from six meat sellers. The samples were then analyzed using analysis of variance (ANOVA), followed by an LSD test to determine significant differences. The results revealed that the factors of trader type, location, and the interaction significantly affected (P<0.05) on the pH value, tenderness, and color of the meat. The factors of Trader type and location significantly affected (P<0.05) the cooking shrinkage of the meat. While the interaction showed no significant effect (P>0.05) on the cooking shrinkage of the meat. Trader type significantly affected (P<0.05) the a* color value of the meat, while location and its interaction showed no significant effect (P>0.05) on a*. Trader type showed no significant effect (P>0.05) on the b* color value of the meat, while location and its interaction had significant effects (P<0.05) on the b* color value of the meat. These results indicate that large traders tend to have better meat quality than small traders, with higher average pH and tenderness and lower cooking shrinkage. Keywords: Meat Quality; Meatballs; Traditional Market